Older Individuals Meeting Medicare Cochlear Implant Candidacy Criteria in Noise but Not in Quiet: Are These Patients Improved by Surgery?. Issue 2 (February 2017) - Mudery, Jordan A.; Francis, Ross; McCrary, Hilary; Jacob, Abraham
Abstract : Objective: To investigate postoperative hearing outcomes in older patients who qualified for cochlear implant (CI) by Medicare criteria using AZBio sentence tests performed in noise but not in quiet. Study Design: Review of patient records. Setting: University-based otology/neurotology practice. Patients: The senior author performed 136 CI between January 2013 and September 2015. Starting in 2013, CI candidacy evaluation included AZBio sentence tests performed in quiet and noise. For the current study, older patients with preoperative AZBio scores greater than 40% in quiet but less than 40% in noise (+10 or +5 dB signal to noise ratio [SNR]) and follow up >/=6 months were included. Intervention(s): Cochlear implantation in one ear. Main Outcome Measure(s): Pre- versus postoperative AZBio sentence test scores. Results: Fifteen patients with an average age of 73 years (range, 59–91) met inclusion criteria. Preoperative AZBio scores for the implanted ear averaged 47% points in quiet and 9% points in noise (+10 or +5 dB SNR). Preoperative bilateral AZBio scores averaged 70% points in quiet and 24% points in noise (+10 or +5 dB SNR). Postoperative AZBio scores for the implanted ear improved an average of 71% points in quiet and 51% points in noise. Postoperative bilateral hearing improved 23% points in quiet and 27% points in noise. Conclusion: All patients undergoing CI candidacy testing should be tested in both quiet and noise conditions. For those who qualify only in noise, our results demonstrate that cochlear implantation typically improves hearing both in quiet and noise.